Benefit Evaluation of Human Settlements Development Funded by SPL JBIC INP-23 in Indonesia - Muhammad Amin Sunarhadi (Universitas Muhammadiyah Surakarta, 2004)
The Government of Japan and the Government of Indonesia has signed a loan agreement Sector Program Loan (SPL) INP 23 for Settlement Sector (Human Settlement) through the Japan Bank for International Cooperation (JBIC) which is intended to overcome the economic crisis and its impact in Indonesia since 1997. Research this carry out an evaluation of the benefits of settlement activities that have been implemented in order to know how much contribution the benefits of the settlement Sector program implemented through the SPL IVI-23, both the recipient community, relevant agencies that manage the project, and local governments that implement and oversee the development of the project . The survey was conducted by using a regional approach, ex post facto, and institutional. The selection of cities and counties samples were selected based on three things: the completeness of the program, the amount of funds, and the number of packets. Next, the results of the rank- ings were selected based on 1) the highest ranking, middle, and low; 2) distribution based on the distribution of the three parts of Indonesia, the western, central, and east; and 3) exclude conflict areas. The results showed that in general the development and results of settlement construction is quite beneficial for the government and society. Among other things more organized neighborhoods, neighborhoods healthier, improved infrastructure, and increased mobility of society. Special benefit shows the influence of the change in service, use of services, and its impact. Development of clean water service level (L) is satisfactory, the level of use (U) range in the level of useful and very useful, and beneficial impact. Drainage construction provide the level of service (L) is very satisfactory, the level of use (U) ranged between levels is useful and very useful, and beneficial impact. For the construction of basic infrastructure settlement (IS and hi, i) provide the level of service (L) is very satisfactory, the level of use (U) range from useful to extremely useful, and gives effect (B) is useful.